Interaction networks among miRNA, protein, and metabolite fingerprints identify the regulatory networks and key players in the pathogenesis of diabetic cardiomyopathy - Chatterjee, Bhaswati; Thakur, Suman S. (Frontiers in Cell and Developmental Biology, 2025)
Diabetic cardiomyopathy (DCM) is a complication of diabetes and is the main cause of death in diabetic patients. The regulatory networks and key players involved in the pathogenesis of diabetic cardiomyopathy are not clearly known. We selected the miRNA, protein, and metabolite fingerprints that play a significant role in DCM and manually constructed miRNA–protein–metabolite interaction networks from the miRNA–protein and protein–metabolite interaction networks. Furthermore, protein–protein, metabolite–metabolite, and protein–metabolite interaction networks were also constructed. The miRNA–protein interaction included evidence from TarBase and microarrays/HITS-CLIP. The protein–protein, metabolite–metabolite, and protein–metabolite interaction networks were obtained at high confidence scores (≥0.7 or 70%). We proposed that the miRNA–protein–metabolite interaction networks along with their intra- and inter-connected protein–protein, metabolite–metabolite, and protein–metabolite interaction networks formed by miRNA, protein, and metabolite fingerprints such as hsa-mir-122-5p, hsa-mir-30c-5p, hsa-mir-30d-5p, hsa-mir-22-3p, IL6, GSTM2, GPX3, ACADM, GSTM3, LEP, ADIPOQ, INS, CASP1, NLRP3, HADH, ACAT1, PRDX2, PRDX1, TNF, ELAVL1, SERPINA1, A2M, IGFBP7, PRDX6, APOA1, APCS, NPPA, ADAM9, GDF15, ACADVL, ECH1, FGL1, bilirubin, butyric acid (butyrate), octanoylcarnitine (octanoylcarnit.), isoleucine, leucine, alanine, glutamine, L-valine, cytidine triphosphate (ara-CTP), 7-keto-8-aminopelargonic acid (7-keto-8-amino.), creatinine, decanoylcarnitine (decanoylcarnit.), and hexanoylcarnitine (hexanoylcarnit.) are the key players and regulatory networks involved in the pathogenesis of DCM. Notably, we also proposed that the interaction networks formed by miRNA, protein, and metabolite fingerprints involved in the early stage of DCM, such as hsa-mir-122-5p, IL6, FGL1, LEP, ADIPOQ, INS, TNF, IGFBP7, GDF15, GPX3, NPPA, bilirubin, butyric acid (butyrate), and creatinine, are the potential biomarkers and therapeutic targets for the early stage of DCM. To the best of our knowledge, this is the first study of the construction of miRNA–protein–metabolite interactomes in DCM, providing insights into the pathogenesis of DCM.